P Extraction Method and Fertilizer Requirement of Soybean on Typic Kandiudox in Papanrejo, Lampung - DEDI NURSYAMSI; M.T SUTRIADI; UNDANG KURNIA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2004)
Field experiment to select extraction method, determine nutrient availability class, and estimate P fertilizer recommendation for soybean on Typic Kandiudox was conducted in Papanrejo, Lampung. The experiment applied single location approach with two steps of activities. The first step conducted in dry season 2002 was to make artificial soil P status by adding P: 0X (very low), 1/4X (low), 1/2X (medium), 3/4X (high), and X (very high status), where X was amount of P required to attain 0,2 μg P l-1 in soil solution. The second step, conducted in the following season (wet season 2002/2003), was P treatment in each artificial soil P status by using P fertilizer: 0, 20, 40, 80, and 160 kg P ha-1 from SP-36 with 3 replicates. The result showed that Mehlich, Olsen, Truogh, Bray 1, and Bray 2 could be used to estimate P fertilizer requirement for soybean on Typic Kandiudox. Among the extractions, Bray 1 was the best. The levels of soil P availability extracted using Bray 1 were classified into: low (<8 ppm P205), medium (8–20 ppm P205), and high (>20 ppm P2O5), while soil P availability extracted using Bray 2 were <12, 12–36, and >36 ppm P2O5 for low, medium, and high classes, respectively. P fertilizer recommendation for soybean on Typic Kandiudox with low, medium, and high soil P availability classes was 58, 45, and 16 kg P ha-1 or equal to 355, 279, and 97 kg SP-36 ha-1, respectively.